Is alexithymia characterised by impaired interoception? Further evidence, the importance of control variables, and the problems with the Heartbeat Counting Task - Murphy, J; Brewer, R; Hobson, H; Catmur, C; Bird, G (Elsevier, 2018)
Interoception, the perception of one’s internal state, is commonly quantified using the heartbeat counting task (HCT) – which is thought to be a measure of cardiac interoceptive sensitivity (accuracy). Interoceptive sensitivity has been associated with a number of clinical traits and aspects of higher order cognition, including emotion processing and decision-making. It has been proposed that alexithymia (difficulties identifying and describing one’s own emotions) is associated with impaired interoceptive sensitivity, but new research questions this association. Problematically, much evidence attesting to the absence of this association has been conducted using the HCT, a measure affected by various physiological and psychological factors. Here, we present novel data (N = 287) examining the relationship between alexithymia and HCT performance, controlling for a number of potential confounds. Inclusion of these control measures reveals the predicted negative relationship between alexithymia and HCT performance. Results are discussed with regard to difficulties quantifying interoceptive sensitivity using the HCT.